2012
DOI: 10.1152/ajplung.00285.2011
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Stat3 signaling dissociates pulmonary inflammation from emphysema in gp130 mutant mice

Abstract: Interleukin (IL)-6 is a potent immunomodulatory cytokine that is associated with emphysema, a major component of chronic obstructive pulmonary disease (COPD). IL-6 signaling via the gp130 coreceptor is coupled to multiple signaling pathways, especially the latent transcription factor signal transducer and activator of transcription (Stat)3. However, the pathological role of endogenous gp130-dependent Stat3 activation in emphysema is ill defined. To elucidate the role of the IL-6/gp130/Stat3 signaling axis in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 50 publications
(71 reference statements)
4
43
0
Order By: Relevance
“…Equally, we were able to show increased phosphorylation of STAT3 by Western blotting in COPD patients compared with nonsmokers. This finding is consistent with elevated levels of interleukin (IL)-6 that are seen in the induced sputum and lung tissue of COPD patients [5,6] and the fact that IL-6 is recognised to activate STAT3 [7]. In addition, other cytokines, such as interferon-γ, IL-2, IL-12, IL-17 and IL-22, may either stimulate the JAK-STAT signalling pathway or be expressed as a consequence of activation of this pathway.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Equally, we were able to show increased phosphorylation of STAT3 by Western blotting in COPD patients compared with nonsmokers. This finding is consistent with elevated levels of interleukin (IL)-6 that are seen in the induced sputum and lung tissue of COPD patients [5,6] and the fact that IL-6 is recognised to activate STAT3 [7]. In addition, other cytokines, such as interferon-γ, IL-2, IL-12, IL-17 and IL-22, may either stimulate the JAK-STAT signalling pathway or be expressed as a consequence of activation of this pathway.…”
supporting
confidence: 75%
“…While we were able to show an increase in STAT3 phosphorylation by Western blotting in COPD patients compared with nonsmokers, our IHC results did not illustrate this. Intriguingly, RUWANPURA et al [6] were only able to demonstrate an association between activation of STAT3 and inflammation, and not COPD status, when comparing COPD patients to "healthy" smokers using IHC. While this appears to support our data showing no difference in phosphorylated STAT3 staining between COPD patients and smokers, it suggests that as COPD patients display airway inflammation but nonsmokers should not, we should have observed a difference between these two groups.…”
mentioning
confidence: 94%
“…We report that compared with control Kras G12D mice, at 6 weeks after activation of oncogenic Kras, compound mutant gp130 F/F :Kras G12D mice displayed an exacerbated lung adenocarcinoma phenotype, which correlated with enhanced lung cellular proliferation. Among IL6 family cytokines, only IL6 was upregulated in the lungs of gp130 F/F :Kras G12D mice, and lung adenocarcinoma severity in gp130 F/F :Kras G12D mice was suppressed by either homozygous or heterozygous ablation of Il6 or Stat3, respectively, which returns augmented STAT3 activation levels in the lung back to normal (30,32). Notably, sIL6R levels were elevated in the lungs of gp130 F/F :Kras G12D mice, and the specific blockade of IL6 transsignaling using genetic and antibody-mediated approaches ameliorated the exacerbated lung adenocarcinoma phenotype in gp130 F/F :Kras G12D mice.…”
Section: Introductionmentioning
confidence: 99%
“…Emergence of Tregs is critically dependent on IL-6 and transforming growth factor (TGF)-b, factors also closely linked to induction of pathogenic IL17-producing T-cells [379,380]. Given that genetic mutation studies have clearly shown the additional role of IL-6 (signalling via a component of its receptor complex called gp130) to promote fibrosis, this cytokine seems attractive for future research [381][382][383]. Moreover, the capacity of B cell derived IL-6 to trigger autoimmunity [384] further underscores this disease axis.…”
Section: Prospects: Future Research Directionsmentioning
confidence: 99%
“…While this last point seems almost counter-intuitive based on current pathogenesis and treatment regimens there is clear evidence from other fibrotic diseases and from experimental models that inflammation can be dissociated from progressive fibrosis. For example, genetic manipulation of signalling from gp130 (a coreceptor essential for signalling of the IL-6 family cytokines which includes IL-6, IL-11, leukaemia inhibitory factor and oncostatin M) directly indicates that fibrosis and inflammation can be dissociated [382,383]. Therefore, it follows that in LTxassociated obliterative bronchiolitis, there is a great difficulty in knowing whether complete suppression of inflammation as a primary therapeutic goal is intrinsically able to reduce all future risk.…”
Section: Prospects: Future Research Directionsmentioning
confidence: 99%